The Settlement of the Bidding Contest for a Public Task Implemented by Non-Governmental Organisations and Public Benefit Entities Without the Possibility of Initiating an Appeal Procedure - Biniasz-Celka, Danuta (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2020)
The paper focuses on the financial cooperation of public administration bodies with public benefit organisations (PBOs) in the form of delegation or commissioning statutory public tasks. As a result of cooperation, a contract is concluded, which is preceded by an open bidding contest procedure. Nevertheless, there is no provision in the contest procedure which would constitute a substantive law basis for issuing an administrative decision or taking other actions referred to in art. 3(2)(4) of the Act of 30 August 2002 on the Administrative Court Procedure by a public administration body or an appointed contest committee.